PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE FORMASI REGU TEMBAK DISERTAI TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 SAWAHLUNTO - Iqbal, Muhammad - (Pendidikan Matematika, 2014)
The research has the background, that is because of the students who have lessresponsibility in doing the exercise which is given by the teacher and the studentsâmathematical concept comprehension is still low. The purpose of this research isto know âDoes Firing Line Type of Active Strategy influence toward StudentsâMathematical Concept Comprehension at the Eight Grade Students of JuniorHigh School 3 Sawahlunto. The design of this research is the experimentalresearch, with the research plans are pre test and post test. The population of thisresearch is the eight grade students of Junior High School 3 Sawahlunto thatconsists of seven classes. The sampling technique is simple random sampling,with doing normality test, homogeneity test, and average similarity test so thatselected as the sample is VIII5 Class, that is as the experimental class. Theinstrument used in this research is the mathematical concept comprehension test,these are pre test and post test. The test form used in this research is essay test.The technique of data analysis used is the concept comprehension t-test testanalysis and data analysis of studentsâ learning product with mathematicalconcept comprehension indicator. Based on the hypothesis test result, itâs gottenthe tcount =14,38 and ttable = 2,06. The hypothesis is accepted because tcount > ttable,until the hypothesis that is assumed accepted at the real degree Î± = 0,05. To sumup, there is the effect of Firing Line Type of Active Learning Strategy towardstudentsâ mathematical concept Comprehension at the Eight Grade Students ofJunior High School 3 Sawahlunto.